(untitled) (East West Medical College Journal, 2026)
Background: Dengue fever, transmitted by Aedes mosquitoes, is a major public health issue in Bangladesh. Urbanization, poor sanitation, and climate change have fueled its spread, with some cases progressing to severe forms like DHF and DSS. Objective: This study aimed to explore gender differences in socio-demographic, clinical and laboratory characteristics of dengue patients in Bangladesh and their correlation with disease severity. Methods: This cross-sectional study included 135 dengue patients from a hospital in Dhaka, Bangladesh, diagnosed clinically and confirmed by laboratory tests between June and December 2023. Data on demographics, clinical symptoms, vital signs, and laboratory results (e.g., platelet count, RBC, hemoglobin, liver function tests) were collected. Statistical analyses were performed using SPSS software, with p-values calculated for gender-based comparisons. Results: Of the 135 patients, 73% were male and 27% female. Fever (94%), muscle and joint pain (96%), headache (86%), and nausea (87%) were the most common symptoms. Females reported significantly more headaches (100%) than males (78.79%, p = 0.03). No gender differences were found in vital signs, but males had significantly higher red blood cell count (RBC), hemoglobin, and hematocrit levels (p < 0.01). Platelet count was higher in females (160,000/µL), but the difference was not significant (p = 0.68). Correlations showed that lower platelet counts were negatively correlated with higher dengue-specific antibodies (IgM and IgG), suggesting a potential early indicator of disease progression. Strong positive correlations were found between RBC count and hemoglobin (r = 0.84, p < 0.01), and liver enzymes (AST, ALT) with bilirubin (r = 0.49, p < 0.01). Conclusion: This study underscores the importance of early detection, highlighting gender differences in symptoms and the potential of platelet counts, antibodies and liver markers in predicting dengue severity and guiding management. EWMCJ Vol. 14, No. 1, January 2026: 48-55